Wheel-like Ln6 luminescent lanthanide complexes covering the visible and near-infrared domains. Issue 31 (24th July 2020) - Sun, Ou; Chen, Peng; Li, Hong-Feng; Gao, Ting; Yan, Peng-Fei
Abstract : Luminescence properties of wheel-like lanthanide complexes. Abstract : The syntheses of pure wheel-like 4f lanthanide complexes are challenging because of the variable and high coordination numbers as well as poor directionality of the lanthanide ions. Therefore, a multifunctional ligand, salicylhydroxamic acid (H3 shi), with various coordination sites is deliberately selected for the construction of lanthanide complexes. At the same time, it is found that the ligand can successfully sensitize the lanthanide centers, exhibiting their characteristic emission. A series of wheel-like complexes are synthesized by using metal to ligand stoichiometry (Ln : H3 shi : 2-pyca) with a ratio of 1 : 1 : 2, namely, [Ln6 (H2 shi)6 (2-pyca)12 (CH3 CN)4 ] (Ln 6 ; Ln = Nd, Sm–Er, and Yb). Single-crystal X-ray diffraction shows that the Eu 6 complex is formed as a hexatomic core with dimensions of approximately 18 × 18 × 13 Å. The powder X-ray diffraction analysis demonstrates that all other isolated complexes are isostructural. The analysis of the luminescence properties of these complexes shows typical metal-centered emission bands from the visible (Sm 3+, Eu 3+, Tb 3+ and Dy 3+ ) to near-infrared (Nd 3+, Ho 3+, Er 3+ and Yb 3+ ) ranges. Sm 6 and Tb 6 exhibit orange and bright-green emission in the visible region, respectively. Eu 6 and Dy 6 exhibit co-luminescence of the corresponding Ln 3+ ions and the ligands. Nd 6 , Ho 6 , Er 6 and Yb 6 exhibit characteristic sharp emission bands in the NIR range.